Uma arquitetura de controle de acesso para internet das coisas - Cesar, Rogério Lopes Vieira (2022)
The Internet of Things is an approach that considers communication between various devices, services, software, objects, and "things"where information is shared and exchanged. The idea of the IoT paradigm is multidisciplinary and heterogeneous, which makes it challenging to ensure reliability in environments that use such technology. Thus, studying how access control behaves in relation to availability becomes critical to providing efficient and reliable services by providing resources when needed, for the time needed, and to the right people. In this paper, we propose an approach that seeks to improve availability in IoT environments through the use of access control techniques and using a decentralized edge computing-based architecture. Thus, the goal is to regionalize and optimize data exchange using a GraphQL-based query language to reduce excessive data searching. We present a performance analysis in which we compare computational resource usage (CPU and Memory), latency, throughput and error rate in resource requests, and the results point to an improvement in availability when access mechanism is used compared to not using it in most of the investigated frameworks, being the scenario that adopts 100 access policies the one that obtained better effects, compared to the scenarios that use 10, 500 or 1000 policies.